O jogo de máscaras na cena política: construção e desconstrução do ethos em debate presidencial televisivo - Serralvo, Flávia Silveira (2011)
This work, based on the Critical Discourse Analysis (CDA) studies, intends to investigate how the participants of a television political debate create a favorable image for themselves, and, at the same time, put in check the adversary s positive image. Based on the tridimensional model idealized by Fairclough (2001), we analyze the argumentative strategies used by the candidates to construct their ethos and to deconstruct the opponent s ethos. Moreover, we observe, as well, how the candidates divide their time between these two strategies, in other words, if there is a balance or the predominance of one. Our units of analysis are the oral texts of the candidates for president in 2006, Geraldo Alckmin (PSDB) and Luiz Inácio Lula da Silva (PT), during the last debate aired by TV Globo. The hypothesis is that the place taken by each candidate, in the context in which the debate is inserted (situation versus opposition), determines the posture adopted in their speech. Corpus analysis enabled to conclude that, in general, Lula has devoted more time to work his own image than to deconstruct the opponent s; Alckmin, on the other hand, spent more time deconstructing his rival s ethos than constructing his own